Al jugar con las palabras se multiplican mundos — análisis de los juegos literarios y de lenguaje en Tres tristes tigres de Guillermo Cabrera Infante - Kobiela-Kwaśniewska, Marta (Romanica Silesiana)
This article can be classified as the one belonging to the broad area of “literary and language plays on words’’ due to its multilevel interpretation of the ludic character of literature in the novel entitled Tres tristes tigres, written by the Cuban writer Guillermo Cabrera Infante, who makes the everyday language of the Havana at the end of the 1950s the object of a play on words, and matter at the same time, which does a literary recreation through its poetisation of the colloquial language. The language, as well as literature, is a pure play on words, which, in turn, destroys in the TTT (Three Trapped Tigers) the traditional canon of the novel and creates a work of literature open to multiple interpretations and which needs an active poliglot reader able to descipher the net of allusions and references to other literary works. The mechanism of the literary play on words is based on parody (of the language itself, of the work of other Cuban writers, of American cabaret, of business celebrities, of the stories related by the characters present in the novel, and of their clumsy English-Spanish translation), on a variety of different points of view that turn the novel into a polyphonic one, on the presence of a stereotype and irony. Moreover, the play on words (anagrams, palindromes, neologisms, polysemy and ambiguity) undergoes an analysis characterised by a polyperspective interpretation of the novel. While talking about the innovative character of the novel, being an example of a new Latin American novel, we present its above-mentioned features and we also do quite a detailed analysis of one of its chapters entitled in Spanish Los visitantes, which best reflects the principal intention of Cabrera Infante: to make everyday language the main character by means of playing with it, and in this way to create a multitude of realities. Key words: Hispano-American language novel, Guillermo Cabrera Infante, Three Trapped Tigers, polyphony, literary and language play on words, parody.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />